2021
DOI: 10.1002/smtd.202001165
|View full text |Cite
|
Sign up to set email alerts
|

Synergies of Fe Single Atoms and Clusters on N‐Doped Carbon Electrocatalyst for pH‐Universal Oxygen Reduction

Abstract: Single atomic metal–N–C materials have attracted immense interest as promising candidates to replace noble metal‐based electrocatalysts for the oxygen reduction reaction (ORR). The coordination environment of metal–N–C active centers plays a critical role in determining their catalytic activity and durability, however, attention is focused only on the coordination of metal atoms. Herein, Fe single atoms and clusters co‐embedded in N‐doped carbon (Fe/NC) that deliver the synergistic enhancement in pH‐universal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 47 publications
2
79
0
Order By: Relevance
“…3c). 48 Sun et al developed a practical synthesis method to produce isolated single platinum atoms and clusters (ALDPt/NGNs) using the atomic layer deposition technique. 49 We believe that more and more effective SACCs will be designed with the continuous development and improvement of various synthetic strategies.…”
Section: Single Atomic Site-clusters (Saccs)mentioning
confidence: 99%
“…3c). 48 Sun et al developed a practical synthesis method to produce isolated single platinum atoms and clusters (ALDPt/NGNs) using the atomic layer deposition technique. 49 We believe that more and more effective SACCs will be designed with the continuous development and improvement of various synthetic strategies.…”
Section: Single Atomic Site-clusters (Saccs)mentioning
confidence: 99%
“…Reproduced with permission, 2017, American Chemical Society. (F) Schematic illustration of the synthetic mechanisms for Fe SAs embedded in N‐doped carbon, and FT profiles of Fe K‐edge k 2 ‐weighted EXAFS data and wavelet transforms for EXAFS signals 61 . Reproduced with permission, 2021, Wiley‐VCH…”
Section: Structures and Modifications Of Nanostructured Carbon Materialsmentioning
confidence: 99%
“…Ru SA‐embedded nitrogen‐doped carbon by employing uncoordinated amine groups on MOFs can provide the atomically isolated dispersion of Ru SA on carbon structure and synergistic effect with Ru sites for electrocatalytic properties. Lee et al also synthesized an iron (Fe) SA‐loaded N‐doped carbon matrix by the carbonization process with Fe salts and glucosamines as SA and doping sources, respectively, as well as sodium chloride as hard templates in Figure 2F 61 . These Fe SA/carbon composites revealed the atomically isolated FeNC sites on carbon matrix, which deliver the excellent catalytic activities in universal pH range.…”
Section: Structures and Modifications Of Nanostructured Carbon Materialsmentioning
confidence: 99%
“…They have good environmental durability, high electrical and proton conductivity but regrettably poor active catalysts in acidic condition. [29][30][31] Previous research has shown that electron divert from Fe/NC to their supported Pt NPs weakens the adsorption intensity of Pt surface for O 2 , consequently enhancing inherent activity of Pt for ORR. [32] However, the formation of such Fe/NC supported Pt NPs (PtÀ Fe/NC) catalyst is not an easy task due to the commonly used of surfactants and capping agents.…”
Section: Introductionmentioning
confidence: 99%